Development of STEM-Based Instructional Materials to Foster Students’ Science Process Skills on Light Waves - Khairiyah, Abidatul; Mastuang, Mastuang; Misbah, Misbah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Developing students’ science process skills (SPS) in secondary physics remains challenging in resource-limited classrooms, particularly when light-wave learning is dominated by teacher-centered instruction and procedural problem solving. This study aimed to develop and evaluate STEM-based instructional materials for Grade XI light-wave learning by examining their validity, practicality, effectiveness, SPS achievement, and STEM product performance. A research-and-development design using the ADDIE model was employed. The materials consisted of lesson plans, student worksheets, an achievement test, and teacher materials. A small-scale feasibility trial involved 25 Grade XI students at a senior high school in Banjarmasin, Indonesia, across three 90-minute meetings on diffraction, interference, and polarization. Data were collected through expert validation, lesson-plan implementation observations, a 20-item pre-test and post-test, worksheet-based SPS rubrics, and STEM product assessment. Validity was analyzed using mean expert ratings, reliability using percentage agreement, practicality using implementation scores, and effectiveness using normalized gain. The lesson plans, achievement test, and teacher materials showed good validity, with scores of 2.98, 3.00, and 2.87, respectively, while the student worksheets showed fair validity (2.76) with acceptable reliability (PA = 0.60–0.83). Practicality increased from 3.61 to 3.93 across the three meetings. Students’ mean score improved from 39.00 to 71.90, yielding a moderate N-Gain of 0.54. SPS achievement was generally skilled to very skilled, although operationally defining variables declined to 1.65 in the final session. Students also produced 3D glasses with good-to-very-good performance in planning, construction, and evaluation. The developed materials are feasible for SPS-oriented light-wave learning, but future revisions should strengthen worksheet scaffolding, quantitative problem-solving support, and longer implementation cycles.